Indicadores de aderência entre planos de médio e curto prazo - Eleutério, Rodrigo dos Santos; Melo, Reymard Sávio Sampaio de (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
In the Last Planner® System of Production Control, there are several indicators that are used to measure the efficiency of the technique according to the planning levels (long, medium and short terms), but treated in isolated ways. Typically, there is a lack of coherence, especially between medium and short-term plans. Thus, this study aims to broaden the discussion initiated in previous studies and propose a methodology to evaluate this adherence using indicators. The paper included the analysis of the Production Planning and Control model, and the medium and short-term plans of a residential project located in Natal/RN, resulting in various forms of lack of adherence between the plans, which can lead to wastes to the project's schedule and costs. The main contribution of the research is the improvement of the adherence indicators, in order to reflect the information in a more complete and comprehensive way.